Analisis Karakteristik dan Kepribadian Ideal Guru Bimbingan dan Konseling dalam Meningkatkan Kualitas Bimbingan dan Konseling di Kota Palu - Fitriani, Dian; Arifyadi, Azam; Hasan, Hasan (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The research aims to determine the personality of the ideal guidance and counseling teacher according to students so students feel enthusiastic about receiving guidance and counseling services at school. The research method used by the author is a qualitative method with a descriptive approach, namely by collecting data as it is from a symptom of a phenomenon that existed when the research was carried out. The data and data sources in this research are 300 State High School students in Palu City, using survey techniques. The research instrument used in this research was the ideal guidance and counseling teacher personality questionnaire. Data analysis techniques are carried out by collecting, analyzing, and interpreting data, which will be concluded as research results. This research concludes that the personality tendency of the ideal guidance and counseling teacher for high school students in Palu City is in the ideal category of (53.67%). The research found that of the 11 indicators considered to determine whether a guidance and counseling teacher is ideal, three indicators are the most chosen by students: warmth, patience, and honesty. The highest indicator of students' assessment of the guidance and counseling teacher's personality lies in the warm indicator, with an average value of 10.84.